Development of a novel phosphoramidite-selenide ligand for Pd-catalyzed asymmetric allylic substitution. Issue 37 (14th September 2022) - Feng, Bin; Fang, Pei-Wen; Lan, Gui-Man; Peng, Li-Yan; Liang, Lu-Fang; You, Ge-Yun
Abstract : A novel chiral P, Se-heterodonor ligand has been designed and prepared through an efficient and simple operation. This ligand can be successfully applied to Pd-catalyzed asymmetric allylic substitution with C- and N-nucleophiles. Abstract : A novel chiral P, Se-heterodonor ligand has been designed and prepared through an efficient and simple operation. This ligand can be successfully applied to Pd-catalyzed asymmetric allylic substitution with C- and N-nucleophiles, producing a diverse range of chiral allylic products in high yields and enantioselectivities (up to 99% yield and 95% ee).